Rethinking systemic change in practice - perspectives from NUTEC-MD in northern Uganda - Koleros, Andrew (BEAM Exchange, 2016)
Document description This document is currently being finalised and will be published shortly. Please try again soon. Recent research by The BEAM Exchange seeks to understand theoretical perspectives on how market systems approaches can contribute to inclusive economic development through systemic change. It produced three main insights. Economies are evolving systems, building on the mechanisms of variety creation, selection and amplification. Current economic performance, including aspects like the inclusiveness of growth and economic evolution, are shaped by the ability of a society to explore different options for institutional arrangements and adjust them over time. This process of evolution is complex. While some aspects can be designed and managed, others need to be explored through a process of learning and adjustment. This paper responds to these insights by providing a practitioner perspective through the lens of one programme: “Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD)”, implemented by Palladium Group. It begins with a brief introduction to the programme and key aspects of its design phase. It then provides a summary of the three main research insights, with reflections on their applicability for programme design based on the NUTEC-MD experience. Finally, it provides some conclusions for the wider practitioner community based on this case.